Pola Komunikasi Interpersonal Konselor Pada Pengguna Narkoba Di Panti Rehabilitas Bahri Nusantara Kota Medan - Jeni Angelia Silitonga; Nina Siti Salmaniah Siregar; Taufik Wal Hidayat (Jurnal Ilmu Pemerintahan, Administrasi Publik, dan Ilmu Komunikasi (JIPIKOM), 2022)
The title of this research is Counselor Interpersonal Communication Pattern on Drug Users at Bahri Nusantara Rehabilitation Center, Medan City. Abuse of narcotics and dangerous drugs (drugs) in Indonesia. In recent years, drugs have become a serious problem so that it has become a national problem. The method used in this study is a qualitative method, collecting data using interviews, observation, and documentation. Based on the results of the research conducted, it is obtained: That the communication pattern is carried out face-to-face between counselors and addicts, so that a more familiar feeling arises to be able to find solutions to problems that occur, related to narcotics. Then the obstacles that occur in counselors where narcotic addict patients are less open, explain the problems they are experiencing, so that the counselor cannot find out what causes the actual patient to happen. Meanwhile, in addicts, there is still a lack of confidence in expressing their problems. So that it has not been maximally disclosed to the counselor.